Returns to Investment in Education : A Decennial Review of the Global Literature - Psacharopoulos, George; Patrinos, Harry Anthony (Taylor and Francis, 2018)
In the 60-plus year history of returns to investment in education estimates, there have been several compilations in the literature. This paper updates Psacharopoulos and Patrinos and reviews the latest trends and patterns based on 1120 estimates in 139 countries from 1950 to 2014. The private average global return to a year of schooling is 9% a year. Private returns to higher education increased, raising issues of financing and equity. Social returns to schooling remain high. Women continue to experience higher average returns to schooling, showing that girls’ education remains a priority.